Spectrum of SARSCOV2 infection with the efficacy of Covaxin and Covishield vaccines during third wave of COVID-19 pandemic: an experience of a densest state of India - Saha, Rajib (International Journal of Research in Medical Sciences, 2022)
Background: Study was conducted to assess the trend or characteristic of SARSCOV2 infection during 3rd wave of pandemic and to compare the efficacy of Covaxin and Covishield Vaccines. Methods: This descriptive cross-sectional study was conducted with a mixed-method approach (Explanatory sequential mixed method) among the SARSCOV2 infected patients of West Bengal, India on the month of January 2022. In quantitative analysis 277 SARSCOV2 infected patients who were detected as COVID positive within January, were selected randomly from the secondary data source (collected by 20 general practitioners). In qualitative analysis, 11 patients from different categories were interviewed in-depth over the telephone to explain the quantitative data. Bivariate analysis (Mann Whitney U or Kruskal Wallis test) was used as per applicability. Kaplan Meir plot compared the efficacy of Covaxin and Covishield vaccines. Results: Most commonly presented symptom were low-grade fever (78.7%), a mild cough (41.9%), mild cold (62.4%), sore throat (41.9%), body ache (47.3%), and headache (33.2%). Few patients had experienced breathing difficulty (1.4%) and hospitalization (1.1%). Mann Whitney U test significantly (p<0.001) justified that Covaxin receivers have infected in late (median 161 days) comparison to other vaccines receivers (Covishield and Sputnik V median 129 days and 115 days respectively). This finding was also demonstrated in Kaplan Meir Plot. Conclusions: During the 3rd wave of the pandemic, SARSCOV2 infected patients commonly presented with milder symptoms, minimal hospitalization and without any case fatality. Delaying of infection has been observed more among Covaxin receivers compared to others.